Can Path Dependence Explain Institutional Change? Two Approaches Applied to Welfare State Reform - Bernhard Ebbinghaus (Max Planck Institute for the Study of Societies, 2005)
Path dependence as a concept in institutional theories has become increasingly popular in economics and other social sciences. The key idea is that in a sequence of events, the latter events are not (completely) independent from those that occurred in the past. Yet, common usage of the concept often subsumes two markedly different models and approaches to understand historical sequencing. The two main processes of the past shaping the future - diffusion and developmental pathways - must be distinguished analytically. This paper juxtaposes (1) the unplanned 'trodden path' that takes shape through the subsequent repeated use by other individuals of that spontaneously chosen path, and (2) the ?branching pathways? or juncture at which one of the available alternative pathways must be chosen in order to continue a journey. Furthermore, the typical approaches and their explanatory purchase are discussed in reference to explanations of institutional change. The paper shows that the first path dependence theorem is too deterministic and inflexible, whereas the second approach is sufficiently supple to analyze various forms of institutional change. – – Pfadabhängigkeit wird in den Sozial- und Wirtschaftswissenschaften zunehmend als Konzept institutioneller Theorien angewendet. Der Grundgedanke ist, dass in einer Sequenz von Ereignissen (oder Entscheidungen) spätere nicht (vollkommen) unabhängig von vorangegangenen sind. Jedoch wird in gängigen Anwendungen des Konzepts oft versäumt, nach zwei äußerst unterschiedlichen Verständnissen historischer Sequenzen zu differenzieren. Die zwei Prozesse der Strukturierung der Zukunft durch die Vergangenheit - Diffusionspfade und Entwicklungspfade - sollen analytisch getrennt werden. Dieser Aufsatz unterscheidet (1) den zufälligen 'Trampelpfad', welcher durch die vermehrte Benutzung eines Pfades spontan entsteht, von (2) dem ?Scheideweg?, an dem einer der möglichen Pfade gewählt werden muss, um den Weg fortzusetzen. Im Weiteren wird der Erklärungsbeitrag der beiden Ansätze in Bezug auf die Erklärung institutionellen Wandels erörtert. Es zeigt sich, dass das erste Pfadabhängigkeitstheorem zu deterministisch und inflexibel ist, der zweite Pfadabhängigkeitsansatz hingegen offen genug, unterschiedliche Formen institutionellen Wandels zu analysieren.
Keywords: 300